Hubungan Self Efficacy dan Dukungan Sosial dengan Subjective Well-Being Korban Penyalahguna Napza di Balai Rehabilitasi Sosial Napza Insyaf Medan - Berliana Silalahi; Abdul Munir; Abdul Murad (Universitas Medan Area, 2019)
This research aims to look at the relationship between Self Efficacy and Social Support with the Subjective Well-Being of Drug Users at the Social Rehabilitation Center for Victims of Drug Abuse